HUBUNGAN ANTARA KETUBAN PECAH DINI TERHADAP KEJADIAN PERSALINAN PREMATURE DI RUMAH SAKIT UMUM DAERAH KOTA PRABUMULIH TAHUN 2021 - Rani Oktarina (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2023)
Premature rupture of membranes is the rupture of the membranes before there are signs of labor starting and waiting for 1 hour has not occurred. The purpose of the study was to determine relationship between premature rupture of membranes and the incidence of premature labor at the Prabumulih City General Hospital in 2021. The research method was analytic, using a cross sectional approach. The population of this study were all mothers giving birth at the Prabumulih City Regional General Hospital in 2021. The sampling in this study used a random sampling technique, which was 326 respondents. The research instrument is a checklist. The results of the study based on univariate analysis showed that there were 62 respondents (19%) whose mothers gave birth prematurely and 264 respondents (81%) who did not give birth prematurely, there were 72 respondents (22.1%) who were diagnosed with premature rupture of membranes and 254 respondents (77.9%) who were not diagnosed with premature rupture of membranes. From the bivariate analysis, it is known that from 72 respondents who were diagnosed with premature rupture of membranes, there were 41 respondents (12.6%) who experienced premature labor and 31 respondents (9.5%) who did not experience premature labor, while from 254 respondents who were not diagnosed with premature rupture of membranes. there were 21 respondents (6.4%) experienced premature delivery and 233 respondents (71.5%) did not experience preterm delivery. In conclusion, there is a significant relationship between premature rupture of membranes and premature labor with a P value of 0.000 < 0.05. Keywords: premature labor, premature rupture of membranes